"Fairy Tale for Pioneers": Deconstruction of Official Ideology in Memories About Artek 1960s–1980s. Issue 3 (2nd July 2016) - Kozlova, Anna
Abstract : This article focuses on the memories of the Soviet pioneer camp Artek among camp leaders and Pioneers who visited this camp in the 1960s–1980s. The study examines the interaction between the ideology discourse of the late Soviet epoch about Artek and personal autobiographical memories. Turning to analysis of narrative structure and the pragmatic context of the memories, the article describes why Artek may be understood as a nonideological and—in some cases—non-Soviet project. Artek as a private realization of the "general" communist utopian project had features that enabled some people to perceive (and remember) it as an "exception" from the usual Soviet everyday life (distance from the center, exoticization of nature, material world) and, as a consequence, the social world.